Sri Lanka Malay revisited: Genesis and classification - Ansaldo, Umberto (John Benjamins Publishing Company, 2008)
This paper presents a fresh take on the origins and nature of Sri Lanka Malay (SLM), based on fieldwork data collected in 2003–2005 in Kirinda, in the south-east of Sri Lanka. It departs from previous studies of SLM in that it is based on substantial recordings of spoken data in natural settings as well as coverage of oral and written history. Work on SLM so far has offered significant insights into the nature of these varieties; due to limited data available, however, some aspects have failed to emerge which are important for our current understanding of SLM. In particular, I aim to show the value of first-hand historical research and natural linguistic data in order to achieve plausible accounts of genesis and accurate classifications of SLM varieties. Based on the combination of these approaches, this paper argues that SLM is the result of trilingual admixture, in which a typological shift from Malay to Lankan grammar occurs.